2018
DOI: 10.1182/blood-2017-07-794529
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomes as a proinflammatory mediator in the development of EBV-associated lymphoma

Abstract: Epstein-Barr virus (EBV) causes various diseases in the elderly, including B-cell lymphoma such as Hodgkin's lymphoma and diffuse large B-cell lymphoma. Here, we show that EBV acts in trans on noninfected macrophages in the tumor through exosome secretion and augments the development of lymphomas. In a humanized mouse model, the different formation of lymphoproliferative disease (LPD) between 2 EBV strains (Akata and B95-8) was evident. Furthermore, injection of Akata-derived exosomes affected LPD severity, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 55 publications
1
94
0
Order By: Relevance
“…BART miRNA were found lacking in 71% of DLBCL cases (49). On the other hand, DLBCL patients with high BART miRNA expression in the blood showed worse prognosis than patients with low expression (50). Although high expression of BART miRNAs is possibly important for malignant transformation of lymphoma, it may be disadvantageous for lymphoma cells survival by escaping immune surveillance.…”
Section: Depletion Of Viral Mirnas In Ebv-associated Tumorsmentioning
confidence: 95%
“…BART miRNA were found lacking in 71% of DLBCL cases (49). On the other hand, DLBCL patients with high BART miRNA expression in the blood showed worse prognosis than patients with low expression (50). Although high expression of BART miRNAs is possibly important for malignant transformation of lymphoma, it may be disadvantageous for lymphoma cells survival by escaping immune surveillance.…”
Section: Depletion Of Viral Mirnas In Ebv-associated Tumorsmentioning
confidence: 95%
“…Further, CD11b + Gr-1 − (monocyte populations) were also increased in the spleen of dasatinib-treated mice. Our group previously found that monocytes and macrophages play a supportive role in tumorigenesis of EBV + lymphoma in a humanized mouse model 37 . Hence, it is also possible that the increase in these cells is a cause of tumor progression in the dasatinib-treated mice.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, the cell fraction of myelomonocytes were investigated since we reported that monocytes and macrophages support EBV-induced tumorigenesis in another humanized mouse model 37 . We observed an increase in CD11b High Gr-1 Low cells in the blood and spleen of the dasatinib-treated mice.…”
Section: Dasatinib Does Not Improve Tumorigenesis Of Lcl-xenograft Micementioning
confidence: 99%
“…Interestingly, the circulating vesicles have been shown to contain nucleic acid in the form of DNA, mRNA and microRNA (miRNA), which may have important biological effects on cells that take up this material (Lefebvre & Lecuyer, ). A recent study found that Epstein–Barr virus (EBV)‐infected cells release exosomes that can influence lymphoproliferation in uninfected cells (Higuchi et al , ). Using two strains of EBV that vary based on their ability to induce lymphoproliferation, EBV‐free exosomes derived from cells infected with the more aggressive viral strain were able to induce lymphoproliferative disease in mice in the absence of EBV itself.…”
Section: Exosomesmentioning
confidence: 99%
“…Using two strains of EBV that vary based on their ability to induce lymphoproliferation, EBV‐free exosomes derived from cells infected with the more aggressive viral strain were able to induce lymphoproliferative disease in mice in the absence of EBV itself. The effect was traced to BamHI fragment A rightward transcript (BART) miRNA transferred in exosomes (Higuchi et al , ). In addition to these important biological effects, the purification and deep sequence analysis of the extracellular vesicles from tumours may provide important diagnostic and prognostic information for patients with NHL.…”
Section: Exosomesmentioning
confidence: 99%